Pengaruh Price Discount, Bonus Pack, dan In-store Display Terhadap Keputusan Impulse Buying (Studi KAsus Pembeli Aksesoris Handphone AA Cell di Jalan Jombang Kota Malang) - Hasan Abdullah; N. Rachma; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to find out the effects of price discount, bonus pack, and in-store display to decision impulse buying. This research uses quantitative research by explanatory research method. Sampling is done by purposive sampling with respondents of mobile accessories buyer at the AA Cell Store, amounting to 80 people. The research instrument used is a questionnaire. Data analysis uses a) instrument test that contains validity and reliability tests, b) normality test, c) multiple linear regression test, d) classic assumption test that contains multicollinearity test and heteroscedasticity test, e) hypothesis test which contains F test and t test. The results of simultaneous analysis of price discount, bonus pack, and in-store display significantly influence the impulse buying. While the results of the partial analysis using multiple linear regression tests shows that price discount has a significant effect on impulse buying, while bonus pack and in-store display have no effect on impulse buying.Keywords: Price Discount, Bonus Pack, In-store Display, Decision Impulse Buying, Accessories Costumer